Chemical Synthesis of Cobalt Nanoparticles and Determination of its Minimal Inhibitory Concentrations and Minimal Bactericidal Concentrations against S. aureus and E. coli - Gupta, Vijayta; Bhardbaj, Monika; Gupta, Annuradha; Verma, Pawan K.; Kant, Vinay (Asian Journal of Science and Applied Technology, 2020)
The indiscriminate usage of antibiotics in the past few years is one of the main reasons behind increased incidences of antimicrobial resistance. The development of potent antibacterial agents to combat this problem is the need of present era. In view of this, in present study, cobalt (Co) nanoparticles were chemically synthesized by standard method. The synthesized Co nanoparticles were tested against the S. aureus and E. coli bacterial strains, and the minimal inhibitory concentrations (MIC) and minimal bactericidal concentrations (MBC) values of Co nanoparticles were determined against these bacterial strains on the day of Co nanoparticles synthesis and after their storage for 30 and 60 days. The Co nanoparticles showed antibacterial actions against S. aureus and E. coli bacterial strains. The MIC values of fresh chemically synthesized Co nanoparticles in this study for S. aureus and E. coli were 140.0 μg/ml and 100.0 μg/ml, respectively. The MBC values of these nanoparticles for S. aureus and E. coli were 260.0 μg/ml and 220.0 μg/ml, respectively. The MIC and MBC values of Co nanoparticles increased on storage of its suspensions for 30 as well as 60 days. It might be considered as potent antibacterial candidate in future after some additional investigations.